Analisis Pengaruh PMDN dan PMA terhadap Perekonomian Provinsi Jambi - Ali Fahmi; Evi Adriani (J-MAS (Jurnal Manajemen dan Sains), 2022)
Economic development carried out by a State aims to realize a prosperous, just and prosperous society. The success of a development can be seen from the development of existing economic indicators, whether it has increased or decreased. Gross Regional Domestic Product (PDRB) is included in one of the indicators of development of a region to see the level of community welfare in a region. PDRB which tends to increase indicates an increase in development and community welfare that continues to improve, while the Declining GDP reflects the decline in development and a decrease in the level of community welfare. Investment is an important factor in determining the level of national income which means it depends on the amount of capital and technology planted and developed in society. Investment activities allow an area to continuously increase economic activity and employment opportunities. This increase in investment in both government and private is very important. The conceptual framework in this study is that the Economy of Jambi Province is influenced by two economic variables, namely; PMDN investment and PMA investment. PDRB as a dependent variable while PMDN and PMA Investment Variable. Descriptive research methods for analyzing data with the Ordinary Least Square (OLS) method is a multiple linear regression. The results showed that PMDN had no significant effect on PDRB. There is a negative relationship between PMA and PDRB. Results of Research Analysis of multiple linear regressions that PMA has a significant effect on Economic Growth in Jambi Province. Based on the results of simultaneous tests that the variables PMDN and PMA simultaneously have a significant effect on the Economy of Jambi Province. While partially variable PMDN has a negative but insignificant effect on the Economy of Jambi Province. Recommendations ; The local government is expected to increase investment in Domestic Investment (PMDN) in Jambi Province through policies by creating a conducive investment climate, simplifying the licensing process, improving infrastructure, and improving the quality of human resources so that it is expected that the value of Investment can increase and can encourage the Economy of Jambi Province.